МАТЕМАТИК МАСАЛАЛАРНИ ЕЧИШДА ДАСТУРЛАШНИ ҚЎЛЛАШ - Бозоров, А.А.; Хуррамов, И.Д. (SCIENCE and SOCIETY, 2024)
This article presents methods for solving mathematical problems based on programs. Students become familiar with the traditional approach, problem solving and creative approaches in applying methods of generalizing analytical and software solutions to mathematical problems in the learning process.
Keywords: least squares method; extreme values of a function; programming basics; million programmers; least value; table of values; system of equations